One-step chemical functionalization of polyethylene surfaces via diarylcarbene insertion - Hu, Z; Chng, S; Liu, Y; Moloney, M; Parker, E; Wu, L (Elsevier, 2018)
Three diarylcarbene derivatives with reactive groups were synthesized and used to graft functional groups onto a plasma-modified polyethylene surface via one-step carbene insertion. The modification is observable spectroscopically, and this one-step strategy provides facile and efficient tool to modify the surface macroscopic properties of low surface energy materials.